RANCANG BANGUNG APLIKASI KELAS EKSEKUTIF YUKNGAJI BOGOR BERBASIS WEB MENGGUNAKAN JAVASCRIPT - Raihan Hafiz Syafi; Samsuri Yahya; Suhendra Anjar Dinata (Sekolah Tinggi Ilmu Komputer El Rahma, 2025)
In the digital era, information technology has become a crucial need in various fields, including da'wah (Islamic outreach), to enhance the effectiveness of message delivery, program management, and participation monitoring. YukNgaji Bogor, a rapidly growing da'wah organization, faces challenges in managing its Executive Class. Manual participant data management via WhatsApp and reporting using spreadsheets lead to inefficiency and difficulties in comprehensive participant progress monitoring. A previous attempt using WordPress encountered server performance issues. This research proposes the design of a web-based system using JavaScript to address these challenges. This E-Kajian system is expected to provide centralized and efficient participant data management, real-time participant progress monitoring, and more accurate and informative study reporting. The implementation of this system aims to improve the operational efficiency of the study program, support the development of YukNgaji Bogor, and extend its benefits to participants.